Characteristics of dissolved organic matter formed in aerobic and anaerobic digestion of excess activated sludge. (February 2017) - Du, Haixia; Li, Fusheng
Abstract: The characteristics of dissolved organic matter (DOM) formed in aerobic and anaerobic digestion of excess activated sludge (EAS) was investigated for three total solid (TS) concentrations (1.2, 2.3 and 5.2%) and three temperatures (5, 20 and 35 °C). The results on the overall concentration of DOM evaluated by TOC showed significantly higher values in anaerobic than aerobic digestion (2.8–6.9 times for TS 1.2–5.2% at 20 °C). Data analysis with a first-order sequential reaction model revealed that higher occurrence of DOM in anaerobic digestion was a result of comparatively faster hydrolysis (1.3–5.5 times for TS 1.2–5.2% at 20 °C; 1.4–49.3 times for temperatures 5–35 °C with TS 1.2%) and slower degradation (0.3–1.0 times for TS 1.2–5.2% at 20 °C; 0.5–8.3 times for temperatures 5–35 °C with TS 1.2%). In aerobic digestion, more humic substances were formed; while, in anaerobic digestion, proteins and aromatic amino acids were the major constituents. For both digestions, except for a few exceptions, proteins and humic substances increased as the TS concentration increased; and increasing the temperature led to a decrease in the content of proteins formed in both aerobic and anaerobic digestion, and an increase in the content of humic substances in the aerobic digestion. The UV-absorbing DOM constituents were highly heterogeneous, and were comparatively larger in anaerobic digestion; and did not change significantly with the TS concentrations and temperatures. Graphical abstract: Highlights: Faster hydrolysis and slower degradation led to more DOM in anaerobic digestion. DOM concentration increased with increases of sludge concentration and temperature. Faster destruction and lysis of cells occurred in anaerobic than aerobic digestion. Higher temperatures promoted cells' destruction in aerobic & anaerobic digestion. More proteins & aromatic amino acids, less humic substances in anaerobic digestion.